2020
DOI: 10.21203/rs.3.rs-22356/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between self-reported walking speed and calcaneal stiffness index in postmenopausal Japanese women

Abstract: Background Osteoporosis and related fractures, a worldwide public health issue of growing concern, is characterized by compromised bone strength and an increased risk of fracture. Here we show an association between self-reported walking speed and bone mass among community-dwelling postmenopausal Japanese women aged 50 years and older. Methods A cross-sectional study was conducted among 1,008 postmenopausal women who underwent a general medical check-up in 2014 and 2016 as recommended by the Japanese governm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The present study showed that grip strength was positively associated with SI. Previous study demonstrated a relationship between grip strength and a higher SI [28]. These results suggest that muscle strength, but not muscle mass, is important for the maintenance of bone mass in postmenopausal women.…”
Section: Table 2 Mean (Sd) Of Stiffness Index According To Fat Mass A...mentioning
confidence: 55%
See 1 more Smart Citation
“…The present study showed that grip strength was positively associated with SI. Previous study demonstrated a relationship between grip strength and a higher SI [28]. These results suggest that muscle strength, but not muscle mass, is important for the maintenance of bone mass in postmenopausal women.…”
Section: Table 2 Mean (Sd) Of Stiffness Index According To Fat Mass A...mentioning
confidence: 55%
“…We applied Pearson's product-moment correlations to assess for correlation among SI, fat mass, muscle mass, log (25(OH)D), log (TRACP-5b), log (PTH), and grip strength. Multiple linear regression analysis was used to explore the effects of fat mass and muscle mass on SI, with adjustment for age, height, comorbidity, current smoking, alcohol consumption, and exercise (Model 1) [11,28,29]. We added log (25(OH)D), log (TRACP-5b), log (PTH), and grip strength to model 1 (model 2) [30][31][32].…”
Section: Statistical Analysesmentioning
confidence: 99%